OLIGOCENE CORAL AND ALGAL REEF AND RELATED FACIES OF VALZEMOLA (SAVONA, NW ITALY) - PATRIZIA FRAVEGA; MICHELE PIAZZA; RUDOLF STOCKAR; GRAZIA VANNUCCI (Rivista Italiana di Paleontologia e Stratigrafia, 2017)
The  terrigenous and carbonate sediments of the transgressive Oligocene cycle of the Tertiary Piedmont Basin outcropping in the area of Valzemola(Savona, western Liguria, Northwest Italy) and which are referable to the Molare Formation are analysed. The terrigenous sequence, represented by breccias, conglomerates and sandstones, overlies with an angular unconformity dolomitic or calcareous-dolomitic lithologies referable to the San Pietro dei Monti Dolomite Formation. These sequences are locally characterized by rich associations of coralline algae and corals, which by providing a stable substrate allowed the development of a true reef build up. Subsequently the bioherm was suffocated by fluvial sandstone and conglomerate. This may be associated with an intensification in the amount of terrigenous material being brought into the basin. A progressive shallowing continues until the introduction of conditions suitable for calcareous deposition in an intertidal or supratidal environment. The analysis of this reef deposit was carried out by examining seven stratigraphic sections. The paleoecological study of the coral fauna and the algal assemblage, the latter characterized by the significant presence either of the genus Lithophyllum, or of Lithothamnion, allowed some hypothesis on the environmental conditions which characterized this sector during the Late Oligocene. Nine different facies could be shown, from those seven directly connected to the reef and two to nearshore environments proving a regressive phase. Facies I: conglomeratic-sandstone representing a stage of colonization in a dominantly terrigenous environment. Facies II: coral framestone, representing a stage of diversification ("an inner reef front" near to the "reef crest"). Facies III: coral bafflestone representing a colonization stage in an "inner reef slope". Facies IV: coral bindstone representing a stage of domination in a "reef crest" environment. Facies V: coral bindstone alternating with floatstone, gives evidence of a colonization stage in a carbonate environment. Facies VI: coral and algae floatstone, representing a facies of accumulated reef debris. Facies VII: coral rudstone, representing an accumulation facies comparable with that of the "rubble & pavement zone" of the back reef. Facies VIII: conglomerates and sands of a shallow marine environment, represent a regressive sequence. Facies IX: massive limestones with undulated-zoned structures, rhizoliths, calcite veins and pisoliths, evidence of an intertidal or supratidal environment.